2022
DOI: 10.3389/fphar.2022.908128
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects and Mechanisms of Yinchen Linggui Zhugan Decoction in HFD-Induced Nonalcoholic Fatty Liver Disease Rats Based on Network Pharmacology and Experimental Verification

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease, characterized by excessive accumulation of hepatocyte fat. However, there is no exact and effective pharmacotherapy for NAFLD. Yinchen linggui zhugan decoction (YLZD) has been widely used to treat NAFLD. Nevertheless, its pharmacological and molecular mechanisms have not been clearly elucidated. This study was carried out to investigate the active components of YLZD and explore its potential mechanisms for treating NAFLD by network pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In addition, YLZD can improve liver function in NAFLD rats, significantly reducing AST and ALT levels. Our previous study ( Jiang et al, 2022 ) found that the improvement was more pronounced with increasing the dose of YLZD administration, and no obvious hepatotoxic effects were observed. It follows that YLZD has an effective therapeutic effect on NAFLD and its potential intervention mechanism is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, YLZD can improve liver function in NAFLD rats, significantly reducing AST and ALT levels. Our previous study ( Jiang et al, 2022 ) found that the improvement was more pronounced with increasing the dose of YLZD administration, and no obvious hepatotoxic effects were observed. It follows that YLZD has an effective therapeutic effect on NAFLD and its potential intervention mechanism is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 85%
“…The formulation granule process is made by Beijing Tcmages Pharmaceutical Co., Ltd. (Beijing, China) using Chinese herbal medicine as raw materials through the steps of extraction, separation, concentration, drying, granulation and packaging. The main components of YLZD formula granules were identified as chlorogenic acid, geniposide, isochlorogenic acid B, isochlorogenic acid A, isochlorogenic acid C, aloe-emodin, rhein, glycyrrhizic acid, and emodin by High Performance Liquid Chromatography (HPLC) with the specific corresponding contents of 2.8521, 11.8532, 0.6459, 0.3511, 0.8627, 0.0971, 0.1098, 2.9140, and 0.0088 (mg/g), respectively ( Jiang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…WAC decreased TG content and reduced lipid deposition in liver and HepG2 cells. Although there are no reports of WAC affecting Frontiers in Pharmacology frontiersin.org 13 NAFLD through the PI3K/AKT signaling pathway, it has been shown that chlorogenic acid prevents HFD-induced hepatic steatosis and may achieve this effect by modulating intestinal flora and increasing GLP-1 secretion (Jiang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no approved agents available for use ( Patel et al, 2020 ; Ratziu et al, 2020 ; Huang et al, 2021 ). There is a growing body of evidence indicating that traditional Chinese medicine (TCM) can prevent and treat early-stage NAFLD ( Dang et al, 2020 ; Jiang et al, 2022 ); TCM may therefore complement lifestyle approaches to preventing and treating NAFLD.…”
Section: Introductionmentioning
confidence: 99%